Association between Non HDL/HDL and Framingham Risk Score in Hypertension Population - Wulandari, Angernani Trias; Qodir, Abdul; Soelistyoningsih, Dwi (Jurnal Keperawatan Florence Nightingale, 2025)
Hypertension and dyslipidemia, encompassing both high-density lipoprotein (HDL) and non-HDL categories, are frequently linked with cardiovascular disease. An imbalance in HDL and non-HDL cholesterol levels, such as an increase in LDL, triglycerides, and total cholesterol, has been demonstrated to increase the risk of atherosclerosis, as reflected in the Framingham score. The present study employed a cross-sectional approach to examine the relationship or correlation between the variables. The sample consisted of hypertensive patients who met the inclusion criteria. The data presented herein were obtained through laboratory tests of HDL, LDL, triglyceride, and total cholesterol levels, as well as cardiovascular risk assessment using the Framingham score. The research data were analyzed using Kruskal-Wallis. A statistically significant relationship was identified between the HDL lipid profile, HDL cholesterol, LDL, triglycerides, and total cholesterol with the Framingham score (p < 0.05). The cardiovascular risk score (Framingham score) exhibited an increase concomitant with elevated non-HDL cholesterol levels and diminished HDL in hypertensive patients. The present study found a significant correlation between HDL and non-HDL levels or values and cardiovascular disease risk scores (FRS). These results underscore the significance of monitoring lipid profiles and nursing education in order to prevent cardiovascular complications through comprehensive risk management